Perang Rakyat Palembang: Analisis Sejarah dalam Komik 5 Hari 5 Malam - Meidonia, Annisa; Rochmiatun, Endang; Otoman, Otoman (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2023)
This study seeks to analyze historical elements in the 5 days and 5 nights war that occurred in Palembang in 1947 which was published in a comic and written by H. Asnawi Mangku Alam and explain how the use of comics as historiography using external and internal criticism theory from Leopold von Rangke According to him, in order to achieve the writing of history as it actually happened, it is necessary to record the truth, in order to see the writing of history objectively and to be able to explain the actual events. This research is focused on answering problems, among others, how historical events are conveyed in the comic 5 Days 5 Nights of the 1947 Palembang People's War, how does this comic present historical elements through writers, characters, setting of place and time, and plot, how to use comic media as historiography. This type of research is qualitative research and uses a descriptive method with a literature study approach. This research technique is heuristic, verification, interpretation, historiography.The results of this study indicate that in the comic 5 Days 5 Nights of the Palembang People's War there is a historical element in every day of the war. This comic was also written by H. Asnawi Mangku Alam who is an actor and witness to the history of war. The development of historical writing in Indonesia cannot be separated from western influences, as well as the media which can make historical writing more interesting. History is written as a unit consisting of various facts that are scattered and put together to become cohesive and coherent